Exploring Meaning Through Dominant Sound Patterns in Stephen Crane Poem's "Fast Rode The Knight" - Imelda Sari Manalu; Diva Dea Wildani; Hikmah Alya; Rahmadsyah Rangkuti (Ruang Kata, 2026)
This study aims to analyze the contribution of sound in establishing the meaning of the poem Fast Rode the Knight by Stephen Crane. Sound usage in poetry is not merely associated with aesthetic effects, but in some cases, it may serve as one of the instruments of interpreting the meaning. Therefore, this study tries to find out what consonants and vowels dominate in the poem and whether there is any connection between the sounds and the implied meaning of the poem. In order to accomplish it, a qualitative approach incorporating phonostylistic analysis was used. Data was acquired through repeated readings of the poem and transcribing the sounds into phonetics for each line. Sounds were then classified and analyzed according to their frequency for the determination of the dominant consonants and vowels. From the results, the most dominant consonant sounds in the poem are the /t/, /l/, /s/, /d/, and /n/ sounds, while the most dominant vowel sounds are /ə/, /ɪ/, /ɒ/, /æ/, as well as /i/, /ɔ/, and /aɪ/. Through the sounds that dominate in the poem, the word “lost” can be formed, even though it does not explicitly appear in the poem. The word carries the entire meaning of the poem, where there is a comparison between the heroic description at the start and the ultimate end that depicts the element of loss and incompleteness. From the findings, it can be concluded that sound patterns could also contribute to meaning making and give an additional layer in interpreting poems, other than looking at the text